Pemanfaatan Aplikasi Pembelajaran sebagai Media Intervensi bagi Anak Berkebutuhan Khusus - Tengku Ryan Hidayatullah; Sri Nurhayati Selian (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Children with special needs are a group of children whose developmental characteristics differ from those of typically developing children, thereby requiring educational, psychological, and social services tailored to their specific needs. The term "slow learner" refers to students who possess below-average learning abilities but do not fall into the category of intellectual disability. Slow learners generally have an IQ in the 70–89 range, meaning they require more time than their peers to grasp concepts, process information, and complete academic tasks. For slow learners, the use of learning applications offers the opportunity to learn at their own pace, review material independently, and engage in more concrete and compelling learning experiences. By implementing appropriate interventions, educators can adapt and facilitate learning to make it more accessible and understandable for these students. Learning applications enable the delivery of content in a more engaging manner through the integration of text, images, audio, video, animation, and interactive activities. This multimodal presentation of material helps transform abstract concepts into concrete ones, thereby facilitating comprehension and improving information retention. Planned and sustained implementation is expected to optimize students' learning potential, providing them with better opportunities to develop in accordance with their individual abilities and needs.